Promiscuous recognition of MR1 drives self-reactive mucosal-associated invariant T cell responses - Chancellor, Andrew; Alan Simmons, Robert; Khanolkar, Rahul C; Nosi, Vladimir; Beshirova, Aisha; Berloffa, Giuliano; Colombo, Rodrigo; Karuppiah, Vijaykumar; Pentier, Johanne M; Tubb, Vanessa; Ghadbane, Hemza; Suckling, Richard J; et al. (The Journal of experimental medicine, 2023)
Mucosal-associated invariant T (MAIT) cells use canonical semi-invariant T cell receptors (TCR) to recognize microbial riboflavin precursors displayed by the antigen-presenting molecule MR1. The extent of MAIT TCR crossreactivity toward physiological, microbially unrelated antigens remains underexplored. We describe MAIT TCRs endowed with MR1-dependent reactivity to tumor and healthy cells in the absence of microbial metabolites. MAIT cells bearing TCRs crossreactive toward self are rare but commonly found within healthy donors and display T-helper-like functions in vitro. Experiments with MR1-tetramers loaded with distinct ligands revealed significant crossreactivity among MAIT TCRs both ex vivo and upon in vitro expansion. A canonical MAIT TCR was selected on the basis of extremely promiscuous MR1 recognition. Structural and molecular dynamic analyses associated promiscuity to unique TCRβ-chain features that were enriched within self-reactive MAIT cells of healthy individuals. Thus, self-reactive recognition of MR1 represents a functionally relevant indication of MAIT TCR crossreactivity, suggesting a potentially broader role of MAIT cells in immune homeostasis and diseases, beyond microbial immunosurveillance.